Predictors of Health-Protective and Helping Behaviors during the Covid-19 Pandemic: The Role of Social Support and Resilience - Fontes, Andrea (2022)
The COVID -19 pandemic dramatically affected people’s lives. In this study, we explored the role of social and personal factors underlying individuals’ adaptive responses during the critical onset period of the outbreak. In particular, we tested two models on the mediating role of health-protective behaviors in the relationship between social support, resilience, and helping behavior. A sample of 1085 participants from Portugal and Brazil took part in an online survey during the first wave of the pandemic. First, through an Exploratory Factor Analysis of the health-protective behaviors to prevent contagion by the coronavirus, we identified two distinct dimensions, one aggregating active protective behaviors and the other as avoidant behaviors. Secondly, we found that resilience and active protective behavior sequentially mediated the relationship between social support and willingness to help. In addition, a multigroup analysis showed that this mediational process was similar in both countries. Given the wide range of social and individual factors that may predict prosocial behaviors, we highlight the role of social support on the intention to help through resilience and active protective behaviors.